A Marketing Management Training and Guidance for Gempita Berkarya Group, Banua Rantau Village, Batang Alai District, HST District - Ibrahim Daud; Abdul Kadir; Dini Rusqiati; Yanuar Bachtiar; Zainal Arifin; Ari Irawan; Siti Mahmudah; Dhea Rahada Salsa Dilla (OMNICODE Journal (Omnicompetence Community Developement Journal), 2022)
There are many types of traditional Indonesian cakes. Each traditional cake has its own characteristics. Now, traditional cakes are slowly starting to be replaced by the presence of modern cakes. Entrepreneurs, both individuals and groups of the traditional cake industry, still use traditional marketing management, such as just waiting for consumers to come, their products are less creative. Training and guidance on marketing of traditional cakes was carried out in Batang Alai Village, HST Regency for 20 traditional cake craftsmen